Early bifurcation of the middle cerebral artery - A case report with commentaries on the clinical significance - Andrzej Żytkowski; Edward Clarke; Agata Olszewska; Agata Mazurek; Andrzej Dubrowski; Maciej Radek (Elsevier, 2022)
Background: The middle cerebral artery (MCA) is the strongest branch of the internal carotid artery and its direct continuation. As MCA is one of the principal intracranial vessels, recording cases of its atypical anatomy is fully justified. In the presented report, we described the anatomical variant of the MCA division and discussed the classification, surgical anatomy, and clinical meaning of this finding. Case description: We found the atypical early division of the MCA during routine dissection of the isolated right cerebral hemisphere. Bifurcation of the MCA was located proximally to the limen insulae, 9.4 mm from the vessel's origin. The MCA branched into the thinner superior trunk and thicker inferior trunk. Thus, the M1 segment of the MCA was shorter than usual, and within the M2 segment, two arterial trunks were observed crossing the limen insulae. Conclusions: The knowledge of anatomical variations of cerebral vascularization should be helpful for everyday medical practice and surgical training. The length of the MCA M1 segment can determine the optimal surgical approach for surgical dissecting and clipping MCA bifurcation aneurysms.